Third-order optical nonlinearity in nonstoichiometric amorphous silicon carbide films - Yu, Xiuru; Ding, Baoyong; Lu, Heng; Huo, Yanyan; Peng, Qianqian; Xiu, Xianwu; Zhang, Chao; Yang, Cheng; Jiang, Shouzhen; Man, Baoyuan; Ning, Tingyin (Journal of alloys and compounds, 2019)
This study investigated the third-order nonlinear optical properties of amorphous silicon carbide (SiC) films prepared via magnetron sputtering at room temperature (RT) and annealed at 200 °C–800 °C. The third-order optical nonlinearity was investigated by Z-scan measurement at a wavelength of 1064 nm and a pulse duration of 25 ps. The self-defocusing behaviour was observed in a large nonlinear refractive index n2 ∼10−14 m2/W, which was five orders of magnitude larger than the value of SiC crystals. By fitting the open-aperture data of the Z-scan, we determined the two- and three-photon absorption in the SiC films prepared at RT and in the annealed samples, respectively. The different nonlinear absorption behaviour was probably ascribed to the intermediate states between the conduction and valence bands. •SiC films without hydrogen were prepared at room temperature by magnetron sputtering.•The atom composition and bonds in SiC films can be influenced by annealing process.•Large nonlinear refractive index ∼10−14 m2/W in SiC films was determined at 1064 nm.•Two- and three-photon absorptionbehaviors in the SiC films were observed.